Differences in the level of anaerobic and aerobic components of physical capacity in judoists at different age - Palka, T.; Lech, P.; Tyka, A.; Tyka, A.; Sterkowicz-Przybycien, K.; Sterkowicz, S.; Cebula, A.; Stawiarska, A. (Archives of Budo, 2013)
The main aim of this study is answer to the question of which indices of body`s physical capacity differentiate professional judo from other athletes at different chronological age and sport experience. Material and Methods: The study encompassed 25 professional judoists at the age of senior, junior and cadet, numbered among the best athletes in Poland. The study included the measurements of indices of morphological body build, followed by the Wingate test and graded exercise test to exhaustion. Results: The study results revealed that the groups of judo contestants, varied in terms of chronological age and training experience, did not differ in their maximal aerobic capacity (V°O2max). The groups of athletes differed significantly in terms of time of exercise over the TDMA threshold. Anaerobic capacity, determined by total work (TW) in the Wingate test, differed across the groups of judoists included in the study. The averaged levels of this index were highest in the senior group while the lowest values were found in the group of cadets. Level of phosphagenic capacity, expressed by the results of peak power (RPP), showed the highest levels in seniors. However, no significant intergroup differences were observed for the level of this index. Conclusions: 1. Many years of specific judo training contributes more to development of anaerobic than to aerobic functional capacity. 2. Faster initiation of the anaerobic energy transformations and higher amount of work done over the TDMA during graded exercise test in seniors compared to juniors might affect the course of the judo fight.